2010
DOI: 10.5194/acp-10-5601-2010
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Tropospheric Emission Spectrometer (TES) CO<sub>2</sub> for carbon cycle science

Abstract: Abstract. We present carbon dioxide (CO 2 ) estimates from the Tropospheric Emission Spectrometer (TES) on the EOSAura satellite launched in 2004. For observations between 40 • S and 45 • N, we find about 1 degree of freedom with peak sensitivity at 511 hPa. The estimated error is ∼10 ppm for a single target and 1.3-2. Correspondence to: S. S. Kulawik (susan.kulawik@jpl.nasa.gov) surface sites shows a correlation of 0.60 which drops when TES is offset in latitude, longitude, or time. At these same locations, T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 61 publications
1
101
0
Order By: Relevance
“…For these reasons, CO 2 and H 2 O are simultaneously retrieved with OCS but are tightly constrained. The a priori profiles for CO 2 and H 2 O are estimated from previous retrieval steps, using their absorption bands that are also measured by TES (Kulawik et al, 2010;Worden et al, 2004). The constraint matrices for CO 2 and H 2 O are based on the covariance from their previous estimates.…”
Section: Retrieval Methodologymentioning
confidence: 99%
“…For these reasons, CO 2 and H 2 O are simultaneously retrieved with OCS but are tightly constrained. The a priori profiles for CO 2 and H 2 O are estimated from previous retrieval steps, using their absorption bands that are also measured by TES (Kulawik et al, 2010;Worden et al, 2004). The constraint matrices for CO 2 and H 2 O are based on the covariance from their previous estimates.…”
Section: Retrieval Methodologymentioning
confidence: 99%
“…The Atmospheric Infrared Sounder (AIRS) has achieved more accurate observations of middle-and upper-tropospheric CO 2 concentrations (Crevoisier et al, 2004;Chahine et al, 2005;Maddy et al, 2008;Strow and Hannon, 2008). The Tropospheric Emission Spectrometer (TES) has observed CO 2 concentrations in several vertical layers with high accuracy by taking advantage of its high wavelength resolution (Kulawik et al, 2010(Kulawik et al, , 2013. The Infrared Atmospheric Sounding Interferometer (IASI) has observed upper-atmospheric CO 2 amounts from its TIR spectra (Crevoisier et al, 2009).…”
Section: N Saitoh Et Al: Validation Of Tanso-fts Tir V1 Utls Co 2 Pmentioning
confidence: 99%
“…Work performed from high spectral measurements in the thermal infrared (TIR), such as AIRS (Crevoisier et al, 2003;Engelen and Stephens, 2004;Divakarla et al, 2006;Chahine et al, 2008;Maddy et al, 2008;Xiong et al, 2008), TES (Shepard et al, 2008;Kulawik et al, 2010;Worden et al, 2012) and IASI (Crevoisier et al, 2009;Herbin et al, 2009;Razavi et al;, has demonstrated the sensitivity of these observations to the midtroposphere. Moreover, the OCO's pre-launch studies (Connor et al, 2008;Butz et al, 2009) as well as those from the shortwave infrared (SWIR) instrument SCIAMACHY Noël et al, 2005) have illustrated the ability of such measurements to get information on gaseous concentrations near the surface.…”
Section: Introductionmentioning
confidence: 99%